On the suprathermal distribution in an anisotropic phonon system in He II - Adamenko, I. N.; Nemchenko, K. E.; Wyatt, A. F. G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The equation that describes the suprathermal distribution of high-energy phonons (h phonons) created in anisotropic phonon systems in superfluid helium is obtained. The solution of this equation enables the derivation of the value of suprathermal ratio S as the ratio of the actual distribution to the Bose-Einstein one, its dependences on the momentum of the h phonons, the anisotropy parameters, and the temperature of the low-energy phonons from which the h phonons are created. We analyze this equation to obtain an estimate of the value of the ratio between the h-phonon number density in anisotropic and isotropic phonon systems and draw conclusions about the dependence of S on the relevant parameters.